Global prevalence and genotype distribution of norovirus infection in children with gastroenteritis: A meta‐analysis on 6 years of research from 2015 to 2020. (1st April 2021) - Farahmand, Mohammad; Moghoofei, Mohsen; Dorost, Abolfazl; Shoja, Zabihollah; Ghorbani, Saied; Kiani, Seyed Jalal; Khales, Pegah; Esteghamati, Abdoulreza; Sayyahfar, Shirin; Jafarzadeh, Mehrzad; Minaeian, Sara; Khanaliha, Khadijeh; et al.
Summary: In the post rotavirus vaccine era, norovirus (NoV) plays an increasingly important role in epidemic and sporadic gastroenteritis among children. This study was designed to provide an updated meta‐analytic review of the prevalence of NoV among paediatric patients with gastroenteritis and to clarify the relationship between NoV infection and gastroenteritis. Systematic searches of the literature for potentially relevant studies were carried out from 1 January 2015 to 29 May 2020. The inverse variance method was chosen for weighting of the studies, and the random‐effects model was used to analyse data. To determine the association between NoV infection and gastroenteritis in children, pooled odds ratio (OR) and its 95% confidence interval (CI) were computed for case–control studies. The pooled prevalence of NoV infection among 12, 0531 children with gastroenteritis from 45 countries across the world was 17.7% (95% CI: 16.3%–19.2%). There were 28 studies with a case–control design, and the pooled prevalence of NoV infection among 11, 954 control subjects was 6.7% (95% CI: 5.1%–8.8%). The pooled OR of the association of NoV infection and gastroenteritis was 2.7 (95% CI: 2.2–3.4). The most common NoV genotypes were GII.4 (59.3%) and GII.3 (14.9%). The highest frequency of NoV was found in the age group below 1 year. Our findings indicated a substantial burden of gastroenteritis caused by NoV globally, with GII.4 and GII.3 the major genotypes responsible for the majority of NoV‐associated gastroenteritis cases among children. Younger age and male sex can be considered risk factors for NoV‐associated gastroenteritis among children.